Metode Quantum Teaching sebagai Solusi Alternatif Pembelajaran Bahasa Arab di era New Normal - Maftuhatul Umamah; Abdul Muntaqim Al Anshory; Sutaman Sutaman (Universitas Islam Negeri Palangka Raya, 2020)
This study aims to explain the basic concepts, the implementation and the benefits of the Quantum Teaching method in learning Arabic which is effective in the new normal era. This research is a qualitative descriptive research. Data collection techniques used were observation, interviews and documentation, with qualitative data analysis techniques; Miles and Huberman: data reduction, data display, and conclusion drawing. The results showed that the application of the Quantum Teaching method can increase the students